2021
DOI: 10.1111/iwj.13640
|View full text |Cite
|
Sign up to set email alerts
|

Histological analysis of fat grafting with platelet‐rich plasma for diabetic foot ulcers—A randomised controlled trial

Abstract: Diabetic foot ulcers are often unresponsive to conventional therapy and are a leading cause of amputation. Animal studies have shown stem cells and growth factors can accelerate wound healing. Adipose‐derived stem cells are found in fat grafts and mixing them with platelet‐rich plasma (PRP) may improve graft survival. This study aimed to establish the histological changes when diabetic foot ulcers are treated with fat grafts and PRP. A three‐armed RCT was undertaken of 18 diabetic foot ulcer patients: fat graf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 54 publications
0
8
0
1
Order By: Relevance
“…An RCT further confirmed this dynamic between aaPRP and stem cells. Histological analyses demonstrated improved neovascularization and graft survival in DFU wounds, although these results are not accompanied by a shortened wound healing time 43 . The findings of this literature review have been summarized in Table 2.…”
Section: Current Evidence and Study Resultsmentioning
confidence: 85%
“…An RCT further confirmed this dynamic between aaPRP and stem cells. Histological analyses demonstrated improved neovascularization and graft survival in DFU wounds, although these results are not accompanied by a shortened wound healing time 43 . The findings of this literature review have been summarized in Table 2.…”
Section: Current Evidence and Study Resultsmentioning
confidence: 85%
“…We summarized the basic characteristics of the included studies, as shown in Table 1 . The included studies were published between 2005 and 2023, with five studies from Egypt ( 34 , 38 40 , 48 ), four from China ( 41 , 44 , 45 , 52 ), three each from India ( 32 , 37 , 50 ) and Iran ( 35 , 36 , 51 ), two from the United Kingdom ( 33 , 49 ), and one each from the United States ( 43 ), Pakistan ( 46 ), and Lithuania ( 42 ). The studies included seven different interventions: fat transplantation, fat transplantation +PRP, PRP, conventional therapy (standard care, saline dressing), hyperbaric oxygen therapy, stem cell transplantation, and stem cell transplantation +PRP.…”
Section: Resultsmentioning
confidence: 99%
“…This study demonstrated that five of the patients achieved 100% wound healing (two from the fat only group, two from the fat/PRP group). This concluded the safety of fat grafts in diabetic foot patients however further studies on a greater group of patients need to be done to find out about the effectiveness of this therapy [17].…”
Section: Wounds and Scarsmentioning
confidence: 92%